Neuropsychiatric and Cognitive Sequelae of COVID-19 - Kumar, Sanjay; Veldhuis, Alfred; Malhotra, Tina (Frontiers in Psychology, 2021)
Abstract: Coronavirus disease 2019 (COVID-19) is likely to have long-term mental health effects on individuals who have recovered from COVID-19. Rightly, there is a global response for recognition and planning on how to deal with mental health problems for everyone impacted by the global pandemic. This does not just include COVID-19 patients but the general public and health care workers as well. There is also a need to understand the role of the virus itself in the pathophysiology of mental health disorders and longer-term mental health sequelae. Emerging evidence suggests that COVID-19 patients develop neurological symptoms such as headache, altered consciousness, and paraesthesia. Brain tissue oedema and partial neurodegeneration have also been observed in an autopsy. In addition, there are reports that the virus has the potential to cause nervous system damage. Together, these findings point to a possible role of the virus in the development of acute psychiatric symptoms and long- term neuropsychiatric sequelae of COVID-19. The brain pathologies associated with COVID-19 infection is likely to have a long-term impact on cognitive processes. Evidence from other viral respiratory infections, such as SARS, suggests a potential development of psychiatric disorders, long-term neuropsychiatric disorders, and cognitive problems. In this paper, we will review and evaluate the available evidence of acute and possible long-term neuropsychiatric manifestations of COVID-19. We will discuss possible pathophysiological mechanisms and the implications this will have on preparing a long-term strategy to monitor and manage such patients.